ISLAM, CYBERSPACE AND POST-TRUTH: EPISTEMOLOGICAL PROBLEMS IN THE DIGITAL AGE - Lutfi, Muhammad; Suhermanto Ja'far (UIN Raden Mas Said Surakarta, 2023)
This study describes how Islam responds to the post-truth that frequently appears in the digital sphere, especially when political momentum is involved. Post-truth connects with epistemology since, factually, it is intimately tied to the question of truth. This study provides a paradigm for dealing with post-truth by combining the taxonomy of fake news with the Islamic epistemology of Murtadha Mutahhari. Using the horizon of post-truth detection and the Islamic epistemological horizon, the method integrates Gadamer's horizons. According to the study's findings, post-truth stems from the issue of human cognitive bias, which occurs when people tend to accept what they want to think to be true. Meanwhile, misrepresentation, media bias, information laundering, statistical deceit, manipulation of election results, and similar practices are the main traits of falsehoods in the virtual world. In line with Murtadha Mutahhari's Islamic epistemology, the multiple frameworks of these lies must be challenged with efforts at verification, correspondence, and soul purity.